Prevention Of Violence Against Children In School Environment - Zulfakar (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The next generation of the nation is made up of children who have dreams and aspirations for the future and the progress and sustainability of Indonesia's development. Therefore, children need to be protected by parents, families, communities, and the government. The increasing cases of violence against children in recent years have raised concerns for parents, communities, academics, and practitioners. This is feared to have a negative impact on the future of children and also on the nation. One factor is the environmental situation. It is important for every parent, educator, and community to conduct socialization about violence against children. This needs to be done so that children can understand the importance of this problem, especially in the digital era that continues to develop today. This is also effective in preparing children to go through puberty. Indonesia has had the Child Protection Law and various other regulations related to child protection issues, which normatively provide protection for children to guarantee respect for their rights. Every year, the number of cases of violence against children in Indonesia continues to increase, especially in Central Lombok Regency, which has experienced a fairly worrying increase. The methods used in this community service activity include observation and social interaction with partners. Therefore, it is important to carry out this service by conducting counseling at SDN 2 Mujur, East Praya, Central Lombok. Together with partners, we organize a series of socialization activities to optimize efforts to prevent violence against children in the school environment. The main objective of this activity is so that the community, especially the next generation of the nation, can understand the consequences of violence against children. The impact of this socialization process is that students can gain knowledge and understanding of regulations and efforts to prevent violence against children.